Comparison Of The Effect Of Giving Fe Tablet With Ambon Banana And That Without Ambon Banana On Hemoglobin Levels In Pregnant Women - Fitriani; Asdinar; Tenriwati (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Consuming Ambon bananas is an alternative to speeding up iron absorption because they contain vitamin C. Data obtained from the Bulukumba district health office, namely there were 7597 pregnant women and those suffering from anemia from January to October 2021, namely 1020 people. The total number of pregnant women with anemia is 13.42%. Research Objectives To find out the comparison of the effect of giving Fe tablets accompanied by Ambon Bananas and those without Ambon Bananas on Hemoglobin Levels in Pregnant Women at the Bontobangun Health Center, Rilauale District, Bulukumba Regency. The research design is pre-experimental with a pre-test post-test design approach. The sample size is 40 people. The sampling technique is Consecutive sampling. The research was carried out from December 2022 to January 2023 at the Bontobangun Health Center, Rilau Ale District. Based on the results of the study, it was found that the mean pre-test HB value was higher in the control group, which was 9.26 gr/dl, while the mean post-test HB value was higher in the intervention group, which was 10.96 gr/dl, meaning that there was an increase in hemoglobin levels in both group, namely pregnant women for 14 days in the group that consumed Fe tablets with Ambon bananas and in the group that only used Fe tablets. This shows that there is a mean difference between the intervention group and the control group. The results of the unpaired t test obtained a value of p = 0.003, so it was concluded that there was a significant difference in the mean between the two groups. The conclusion in this study was that there was a significant difference in Hb levels between before and after treatment in both the intervention group and the control group. The research results should be used as a reference in providing additional interventions related to the willingness of pregnant women to get used to consuming Ambon bananas.